A Cross-sectional Survey and Cross-sectional Clinical Trial to Determine the Prevalence and Management of Eye Movement Disorders and Vestibular Dysfunction in Post-Stroke Patients in the Sub-Acute Phase: Protocol - van Wyk, Andoret; Eksteen, Carina A.; Becker, Piet J.; Heinze, Barbara M. (Frontiers in Neurology, 2016)
Introduction Visual impairment, specifically eye movement disorders and vestibular dysfunction may have a negative influence on the functional recovery in post-stroke patients. This type of sensory dysfunction may further be associated with poor functional outcome in patients’ post-stroke. Methods In phase 1, a cross-sectional survey (n = 100) will be conducted to determine the prevalence of eye movement disorders and vestibular dysfunction in patients who sustained a stroke. A cross-sectional clinical trial (n = 60) will be conducted during phase 2 of the study to determine the effect of the combination of vestibular rehabilitation therapy (VRT) and visual scanning exercises (VSE) (experimental group) integrated with task-specific activities compared with the effect of task-specific activities as an intervention (control group) on patients who present with eye movement impairment and central vestibular dysfunction post-stroke. An audiologist will assess (a) visual acuity (static and dynamic), (b) nystagmus, (c) saccadic eye movements, (d) smooth pursuit eye movements, (e) vestibulo-ocular reflex, and (f) saccular, utricular, and vestibular nerve function. An independent physiotherapist will assess (1) cognitive function, (2) residual oculomotor visual performance, (3) visual–perceptual system, (4) functional balance, (5) gait, (6) functional ability, (7) presence of anxiety and/or depression, and (8) level of participation in physical activity. Ethics and dissemination Ethics approval has been obtained from the Ethics Committee of the Faculty of Health Sciences at the University of Pretoria (UP) (374/2015). The study will be submitted as fulfillment for the PhD degree at UP. Dissemination will include submission to peer-reviewed professional journals and presentation at congresses. Training of rehabilitation team members on the integration of VSE and VRT into task-specific activities in rehabilitation will be done if the outcome of the experimental group’s functional performance is clinically and statistically significantly better than the control group on the Barthel Index. Trial Registration Pan African Clinical Trials Registry (PACTR201509001223262).